Luther. Season 3 [videorecording (DVD)] - Kirk, Brian, 1968-; Miller, Sam, 1962 September 28-; Schwartz, Stefan, 1963-; Wilson, Ruth, 1982-; Elba, Idris; Crowley, Dermot; Brown, Warren, 1978- (Warner Home Video, 2013)
In this new mini-series, a twisted fetishist is targeting young women in London. As Luther is called to another case, will the killer escape his grips? Luther faces an even bigger threat as members of his own team will stop at nothing to bring him down. And as a vigilante killer takes justice into his own hands, Luther questions his own sense of morality. Can he continue to walk the thin line between right and wrong, or has he finally met his match?